Primary outcomes of One - Stage repair for interrupted aortic arch at Vietnam National Children’s Hospital - Truong, Nguyen Ly Thinh; Anh, Doan Vuong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objective: This study focuses on primary outcomes of one-stage repair for interrupted aortic arch (IAA) from a single institution in Vietnam. Methods: Between 2012 and September 2017, 27 patients underwent one-stage repair in the Children Heart Center, National Hospital of Pediatrics. Kaplan-Meier survival analysis plotted survival and freedom from reoperation curves from follow-up data. Results: Median age was 53 days (range, 9 days to 5 months) and weight was 3.5 kg (range, 2.3 to 6.5 kg). IAA type A was present in 16 cases (59.3%), and IAA type B in 11 cases (40.7%). Associated anomalies included ventricular septal defect in 20 (74.1%), aortopulmonary window in 4 (14.8%), and truncus arteriosus in 3 (11.1%). Fourteen patients (51.9%) had left ventricular outflow tract obstruction (LVOTO). Median follow-up was 17 months (range, 1 day to 71 months). Survival rates at 30 days, 1 year, and 5 years were 81.5%, 77.6%, and 77.6%, respectively. There were 5 early deaths in the hospital, 4 related to nosocomial infection with positive results in blood culture or endotracheal tube, and one was sudden death. One late death after 4 months was caused by severe pulmonary artery stenosis after total repair of interrupted aortic arch associated with truncus arteriosus. There were 5 late reoperations or balloon angioplasty, with reoperation for LVOTO in 3, right ventricular outflow tract reconstruction in 1, and the other required balloon angioplasty for recurrence of aortic arch stenosis. Conclusion: Primary outcomes of one-stage repair for interrupted aortic arch are safe in our institution. Long-term outcomes evaluation is needed for this complex congenital heart disease.